027 Paediatric emergency department attendances between 2000 and 2009: trends in a large UK Children's Hospital. (14th September 2011) - Lai, J; Mason, S; Burke, D; Julious, S A; Freeman, J V
Abstract : Objectives and Background: There has been an increase in UK demand for emergency department services. This may be attributed to changes in public behaviour or the availability of out of hours services. The objective of this study is to investigate whether these changes are reflected in paediatric cases by identifying patterns in paediatric emergency department attendances (ED) from a large UK urban hospital. Methods: Data relating to admissions and ED contacts were obtained from a large UK Children's hospital from 01 January 2000 to 31 December 2009. Cases were categorised as trauma if the diagnosis text inferred physical (penetrating or blunt) injury. Graphical investigation was undertaken of the mean monthly daily counts of trauma/non-trauma contacts. Results: There were a total of 455 990 contacts made to ED. Of this figure, 46.9% were categorised as trauma overall. There has been a profound increase in hospital admissions from ED (+47.14%), admissions overall (+40.11%) and total ED attendances (+27.11%) throughout this time period. Observing trends for trauma attendances, there was a slight decrease (−11.72%) while for non-trauma attendances, there was a severe increase (+76.71%) in the annual number of attendances. Trends for the average year indicate that for trauma attendances compared to the annual mean, the largest increase and decrease is observed in December (+21.09%) and August (−27.19%) respectively. For non-trauma attendances, the largest increase and decrease is observed in June (+22.48%) and December (−30.97%) respectively. Conclusion: There has been an increase in paediatric emergency department attendances from 2000 to 2009. However, the increase is mainly attributed to conditions categorised as non-trauma rather than trauma. Annual patterns exhibit seasonal variation. In addition, admissions rates from ED from have increased by 47%. Further investigation is required to understand reasons for the rising demand in emergency department services and specifically, the increase in non-trauma attendances and admissions.